The Ekphrasis on the Water Clock: Art, Rhetoric and Measurement of Time in Sixth-Century Gaza. - Talgam, Rina (Scripta Classica Israelica, 2025)
This paper discusses The Ekphrasis on the Water Clock, composed in the sixth century C.E. by Procopius of Gaza. It inspects three facets: 1. The Gaza clock against the background of other clocks in antiquity 2. The artwork of the theatrical display presented in the Gaza clock 3. The rhetoric of Procopius' ekphrasis. The Ekphrasis on the Water Clock exemplifies how the character of ekphrasis is adapted to the item that is described. It appears that Procopius chose to convey his impressions in an objective tone, out of concern that readers might question his credibility and presume the water clock to be an imaginary object. The Ekphrasis on the Water Clock testifies to the great importance of Gaza in the preservation of classical knowledge in Late Antiquity and in fostering this importance within the fields of literature, art, and technology.